Hutchison's Paediatrics - Goel Krishna M, Gupta Devendra K; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2012)
The patterns of childhood disease in the entire world is changing with the advancing knowledge, altering living standards, lifestyle, and rising levels of medical care. In the early stage of child development, the origin of physical and mental health and disease lies. Most of the abnormalities that affect health and behaviour of children are prenatally determined or are determined in the first few years of life by genetic and environmental factors. In this book (3z(BHutchison's Paediatrics(3y (Bsummary of current knowledge of causation and indications where health education and prevention might reduce the burden of childhood ill health is discussed in concise. This book contains thirty eight chapters providing practical advice about the diagnosis, investigation and management of the full spectrum of childhood disorders, both medical and surgical, along with the appropriate techniques and laboratory investigations wherever necessary for advanced diagnosis and up-to-date therapy. It gives an intended and true apprenticeship fashion of teaching to provide a manageable, readable, and practical account of clinical paediatrics for medical undergraduates, for postgraduates specialising in paediatrics and for general practitioners whose daily work is concerned with children care in health and sickness. Many figures illustrating salient concepts summarising clinical findings and treatment results are also provided for better understanding the concepts.s
Keywords: Pediatrics; Electronic books